Recognition of Prior Learning (RPL) as pedagogical pragmatism. (15th November 2017) - Pokorny, Helen; Fox, Stephen; Griffiths, Dave
This case study is located within a joint venture between a University and a College of Further Education, with an explicit mission to bring into Higher Education underrepresented groups, including mature learners and to promote part-time education. Our case study provides a review and evaluation of the successful development of an undergraduate programme in leadership and professional development for experienced learners, two-thirds of which is awarded through the Recognition of Prior Learning (RPL). The case study demonstrates how the research-informed RPL design has enabled the recognition of prior learning in a way that is both true to the students' experience and works within the parameters of quality assurance frameworks. The term used is 'pedagogical pragmatism', i.e. a process that rests on particular combinations of both technical rationality (e.g. adherence to a Learning Outcome focused output which is static and a "given") and professional artistry (differential judgements made about the efficacy of approaches to RPL). The practices are contextual, however we would argue that sharing the conditions that underpin RPL as a specialised pedagogic practice is an important part of moving this agenda forward in the sector.